ANOTHER LOOK AT A POLYNOMIAL SOLUTION FOR ALTERNATING POWER SUMS - Leomarich F Casinillo (Diponegoro University, 2022)
This paper aims to provide a new general explicit polynomial solution on power sums of consecutive positive integers under alternating signs. Moreover, it examines the solution under odd and even number of terms in the series and provides some examples.